Where did Venomous Snakes Strike? A Spatial Statistical Analysis of Snakebite Cases in Bondowoso Regency, Indonesia - Farid Rifaie; Tri Maharani; Amir Hamidy (HAYATI Journal of Biosciences, 2017)
Snakebite envenomation in Indonesia is a health burden that receives no attention from stakeholders. The high mortality and morbidity rate caused by snakebite in Indonesia is estimated from regional reports. The true burden of this issue in Indonesia needs to be revealed even starting from a small part of the country. Medical records from a Hospital in Bondowoso Regency were the data source of the snakebite cases. Three spatial statistical summaries were applied to analyze the spatial pattern of snakebite incidents. The comparison between statistical functions and the theoretical model of random distributions shows a significant clustering pattern of the events. The pattern indicates that five subdistricts in Bondowoso have a substantial number of snakebite cases more than other regions. This finding shows the potential application of spatial statistics for the snakebite combating strategy in this area by identifying the priority locations of the snakebite cases.